Canopy structure in soybean monocultures and soybeansorghum mixtures: impact on aphid (Homoptera: Aphididae) landing rates - Bottenberg, H.; Irwin, M.E. (Oxford University Press, 1992)
Aphid landing rates were monitored with horizontal mosaic green pan traps in monocultures of soybean, Glycine max (L.) Merrill, and in additive mixtures of soybean with dwarf or tall isolines of sorghum, Sorghum bicolor (L.) Moench. Rhopalosiphum maidis (Fitch) colonized sorghum whorls and was the major species caught in pan traps. Weekly aphicide spot applications to sorghum whorls, starting at 36 d after planting, did not suppress R. maidis colonies significantly until after the third application. Landing rates of R. maidis alatae were similar in treated and untreated crop mixtures. The lack of a significant difference may have resulted from immigration of R. maidis alatae from outside the experimental field but inefficient colony suppression may have produced similar results. Mixed cropping reduced landing rates of Aphis gossypii Glover, Aphis helianthi complex, and Lipaphis erysimi (Kaltenbach) on sorghum plants, and R. maidis on soybean plants. Generally, landing rates were equally reduced in the mixtures with tall or dwarf sorghum. The percentage of ground covered by vegetation, which was less in monocultures than in mixtures, proved to be more important than crop height in reducing aphid landing rates. All aphid species landed randomly on soybean and sorghum plants within dwarf sorghum mixtures. However, in tall sorghum mixtures Aphis nerii Boyer de Fonscolombe and A. gossypii preferred to land on soybean whereas Aphis spiraecola Patch landed more often on sorghum. Landing R. maidis alatae did not show a preference for sorghum or soybean in the crop mixtures. Different sensitivities to microclimatic conditions may explain these behavioral patterns.